IMPLEMENTASI DESIGN THINKING UNTUK BUSINESS SUSTAINABILITY USAHA GOKIL (GOSOK KILAT LAUNDRY) - Miswanto, Endhita Asmarani; Pratama, Hanif; Khasanah, Miladiyah; Nidzar, Saifun; Mazia, Lia (LPPM Universitas Nusa Mandiri, 2023)
GOKIL (gosok kilat laundry) is a service-focused business that offers clothes washing & ironing services, this business was founded in 2017 which is located on Jl. Tegal parang Utara 1, RT 006, RW 05, Kel. Tegal parang, Kec. Mampang Prapatan, South Jakarta. there are problems from the GOKIL (Gosok Kilat Laundry) business, namely, not having a clear identity, still using a private house that is used as a residence, incomplete business equipment, and minimal marketing, which is still done only limited to recommendations from customers. This research aims to describe the theoretical stages of Design Thinking applied to GOKIL (Gosok Kilat Laundry) Business in an effort to find appropriate and effective solutions to problems for business sustainability. The method used for this research is a qualitative descriptive approach and uses the design thinking method to analyze problems from an internal and external perspective and in determining solutions, which consists of five stages, namely empathize, define, ideate, prototype, and test. The results of this study indicate that there needs to be a solution to problem solving for business sustainability, so, a prototype proposal is given, namely first making a unique name to attract customer attention and making a business logo in the physical form of a banner, second making social media in the form of Facebook and Whatsapp as a touchpoint with customers as a marketing medium and facilitating the shuttle process, the author also updates the laundry packaging so that it is more environmentally friendly.